Lacrimal gland mucoepidermoid carcinoma with contralateral eye and systemic metastasis: A rare case report and review of the literature - Wu, Yi; He, Weimin (Frontiers in Oncology, 2023)
Lacrimal gland mucoepidermoid carcinoma is very rare. It has a high risk of recurrence and metastasis, however, it rarely metastasizes to the contralateral eye in clinical practice. Here, we present a case of a 52-year-old man with lacrimal gland mucoepidermoid carcinoma who developed multiple recurrences and metastases of another eye and other sites throughout the body after receiving surgical intervention and regular radiotherapy, which will be of ophthalmic interest and unique. Clinical features, imaging findings, histopathology, treatments, and outcomes of this very rare case are provided. A literature review of previously published cases of this disease is performed, with an emphasis on the latest diagnosis and treatment. The prognosis of tumor recurrence and metastasis is poorer, surgery with a negative margin in conjunction with adjuvant therapies is crucial for preventing local recurrence and distant metastasis and enhancing the survival rate.